Enzyme activities of the northern shrimp (Pandalus borealis) exposed to global change drivers - Ella Guscelli; Denis Chabot; Fanny Noisette; Pierre U Blier; Mathilde Chemel; Piero Calosi (PANGAEA, 2025)
Northern shrimp Pandalus borealis from the St. Lawrence Estuary (48° 35 extquotesingle N, 68° 35 extquotesingle W, May 2018) were exposed for 30 days under laboratory conditions to different ocean global change scenarios of temperature (2, 6, or 10 °C), pH (7.75 or 7.40) and hypoxia (100 or 35% relative to air saturation) in isolation and combined. The experiments took place between July 9 and August 20, 2018. The dataset contains the specific activity of energetic metabolism key enzymes measured in female shrimp, expressed as U g?^1 prot.
In: Guscelli, E et al. (2025): Survival, metabolic traits and enzyme activities of the northern shrimp (Pandalus borealis) exposed to combined global change drivers [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.988046